Utilising SWOT Analysis to Improve The Comeptitiveness of UMKM in The Pandemic Era - Naomi Putri Manurung, Theresia (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
In the pandemic era and the highly competitive national and international economic landscape, Micro, Small and Medium Enterprises (MSMEs) are facing challenging times. This is due to the increasingly intense competition in domestic and foreign industries. The government needs to pay greater attention to MSMEs as they are one of the drivers of economic growth, especially in Indonesia. Growing the MSME sector and reducing poverty are signs of successful development. Especially for low-income countries, the expansion of the MSME sector and the reduction of poverty are signs of successful development income per capita. The best tool to help MSMEs decide on marketing plans and forecast changes in the corporate environment is SWOT analysis. Where SWOT analysis can be applied Threats, Weaknesses, and Strengths are internal elements that affect MSMEs. MSMEs internal threats and Opportunity factors arising from competition or outside sources. Four marketing strategies were derived from this research to help MSMEs become more competitive. These strategies include the S-O Strategy of MSMEs, which calls on MSMEs to innovate, create unique features for their goods, and use technology as a tool for sales and promotion.